Laparoscopic or open appendicectomy for suspected appendicitis in pregnancy and evaluation of foetal outcome in Australia. Issue 5 (6th September 2016) - Winter, Nicole N.; Guest, Glenn D.; Bozin, Michael; Thomson, Benjamin N.; Mann, G. Bruce; Tan, Stephanie B. M.; Clark, David A.; Daruwalla, Jurstine; Muralidharan, Vijayaragavan; Najan, Neeha; Pitcher, Meron E.; Vilhelm, Karina; et al.
Abstract : Background: Recent data suggest that laparoscopic appendicectomy (LA) in pregnancy is associated with higher rates of foetal loss when compared to open appendicectomy (OA). However, the influence of gestational age and maternal age, both recognized risk factors for foetal loss, was not assessed. Method: This was a multicentre retrospective review of all pregnant patients who underwent appendicectomy for suspected appendicitis from 2000 to 2012 across seven hospitals in Australia. Perioperative data and foetal outcome were evaluated. Results: Data on 218 patients from the seven hospitals were included in the analysis. A total of 125 underwent LA and 93 OA. There were seven (5.6%) foetal losses in the LA group, six of which occurred in the first trimester, and none in the OA group. After matching using propensity scores, the estimated risk difference was 5.1% (95% confidence interval (CI): 1.4%, 9.8%). First trimester patients were more likely to undergo LA (84%), while those in the third were more likely to undergo OA (85%). Preterm delivery rates (6.8% LA versus 8.6% OA; CI: −12.6%, 5.3%) and hospital length of stay (3.7 days LA versus 4.5 days OA; CI: −1.3, 0.2 days) were similar. Conclusion: This is the largest published dataset investigating the outcome after LA versus OA while adjusting for gestational and maternal age. OA appears to be a safer approach for pregnant patients with suspected appendicitis.